“The Woman Question” as Expressed in the Work of Slovenian Writer Pavlina Pajk, and the Presumed Influence of Western Ideas on Her Work - Badalič, Tanja (Poznańskie Studia Slawistyczne, 2016)
Foreign literary influences, German and Western European in particular, played a pivotal role in the 19th-century Slovenian literary field. During this time, the first female Slovenian authors emerged. Among them was Pavlina Pajk (1854–1901) who continued the tradition of the sentimental novel. Her texts incorporate several topics and motifs associated with the novels of other Western female authors, in particular those of George Sand. Moreover, Pajk was the first Slovenian woman writer who, presumably influenced by Western ideas, started writing about “the woman question”. This article thus presents Pajk’s ideas concerning “the woman question” in her writings.